2014
DOI: 10.4995/wpom.v5i1.2082
|View full text |Cite
|
Sign up to set email alerts
|

Financial performance of Spanish hotels during the crisis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Chain size is often measured via the number of employees hired or the number of establishments in the chain, while hotel size is often measured by the number of rooms. The evidence found in the literature regarding hotel size and performance is not completely clear, although several studies have suggested that larger, individual hotels can achieve higher levels of performance due to economies of scale, higher bargaining power and more possibilities of funding and investment; see, e.g., Claver et al (2007a, b), Kim et al (2013) and Babayan et al (2014). and Arbelo et al (2018) report evidence that large chain hotels achieved a better performance than small, independent hotels.…”
Section: Working Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chain size is often measured via the number of employees hired or the number of establishments in the chain, while hotel size is often measured by the number of rooms. The evidence found in the literature regarding hotel size and performance is not completely clear, although several studies have suggested that larger, individual hotels can achieve higher levels of performance due to economies of scale, higher bargaining power and more possibilities of funding and investment; see, e.g., Claver et al (2007a, b), Kim et al (2013) and Babayan et al (2014). and Arbelo et al (2018) report evidence that large chain hotels achieved a better performance than small, independent hotels.…”
Section: Working Hypothesesmentioning
confidence: 99%
“…and Arbelo et al (2018) report evidence that large chain hotels achieved a better performance than small, independent hotels. Also, Babayan et al (2014) show that the size of a hotel positively affects the total revenue and that establishments with less than one hundred rooms do not seem to manage their assets so well.…”
Section: Working Hypothesesmentioning
confidence: 99%
“…Occupancy levels and achieved average room rates grew steadily, and gross operating profit per available room more than tripled between 2009 and 2017 from €7,514 to 24,320 according to the MHRA (2018) and MHRA (2010). Hotels in similar tourism destinations, such as the Spanish Costas in the Alicante region, only experienced minor improvement during the same period (Babayan et al , 2014). The difference in improvement rate is presented in Table II.…”
Section: Research Backgroundmentioning
confidence: 99%